Disclination dipoles are the Holy Grail for high temperature superplasticity in ceramics. (August 2020) - Moshtaghioun, Bibi Malmal; Bejarano-Palma, José Antonio; García, Diego Gómez
Abstract: A model for high-temperature plasticity of polycrystals controlled by disclination dipoles is proposed that predict a parabolic dependence of the strain rate versus the applied stress. The presence of a precise stationary disclination density explains the origin of plasticity without microstructural invariance, commonly known as superplasticity. The disclination mechanism is universal, although other processes, such as dislocation glide, are superposed to this one in many systems such as metals or metallic alloys. While, in ceramics it is likely to be the only operative mechanism. Activation of disclination dipoles is a necessary condition for plasticity and sufficient one for superplastic yielding. Graphical abstract: Image, graphical abstract